Acetyl-DL-leucine improves gait variability in patients with cerebellar ataxia—a case series. Issue 1 (December 2016) - Schniepp, Roman; Strupp, Michael; Wuehr, Max; Jahn, Klaus; Dieterich, Marianne; Brandt, Thomas; Feil, Katharina
Abstract Acetyl-DL-leucine is a modified amino acid that was observed to improve ataxic symptoms in patients with sporadic and hereditary forms of ataxia. Here, we investigated the effect of the treatment with Acetyl-DL-leucine on the walking stability of patients with cerebellar ataxia (10x SAOA, 2x MSA-C, 2x ADA, 1x CACNA-1A mutation, 2x SCA 2, 1x SCA 1). Treatment with Acetyl-DL-leucine (500 mg; 3-3-4) significantly improved the coefficient of variation of stride time in 14 out of 18 patients. Moreover, subjective ambulatory scores (FES-I and ABC) and the SARA scores were also improved under treatment. Further prospective studies are necessary to support these class III observational findings.